Glutamina e alanil-glutamil-glutamina : síntese química, efeito no transporte de água, eletrólitos e permeabilidade intestinal - Lima, Aldo Ângelo Moreira (1998)
Glutamine (Gin) is the principal source of energy and precursors for protein and nucleotide synthesis in the intestinal epithelial cells. However, Gin is unstable in acidic conditions, which make it dificult to use for diarrhea and malnutrition treatment. The objectives of this study were to develop and synthetize a stable Gin derivative, and to evaluate the impact of Gin and alanyl-glutamyl-glutamine (AGG) on water and electrolytes transport and on intestinal epithelial permeability. The chemical method used to synthetize AGG employed a solid phase reaction. The addition of alanine (Ala) and Gin to the original molecule of Gin completely prevents its degradation in acidic conditions (pH =1) when incubated for 375 h. Gin and Ala were more efficient than glucose (Glu) in the intestinal cotransport of Na+, measured in isolated ileum mounted in Üssing chambers. In the same model, AGG and alanyl-glutamine (Ala-Gln) induced a significant increase in the eletrogenic transport. These substrates caused also a significant increase in the water and electrolytes transport, using the in vivo rat intestinal perfusion. The oral rehydration solution with glutamine (ORS-Gln) completely reversed the intestinal secretion of water and electrolytes in the secretory model induced by choleratoxin (CT = 84 kDa; 1 pg/ml). To evaluate the impact of Gin in the intestinal permeability of children, we developed and utilized the lactulose (L)/manitol (M) test. Thirty eight children with acute diarrhea were selected to participate in a case-control study that was randomized and double-blind. In contrast to untreated controls, children who took ORS-Gln and completed the study, showed a borderline significant reduction in intestinal damage (by L/M test: : 0.1510 ± 0.0974 vs. 0.0741 ± 0.0457, N = 9 pairs, p = 0.056). Thirty high risk children for more diarrheal episodes and/or malnutrition were also selected to participate in a similar study design. Again, in contrast to controls, children in the ORS-Gln group showed a significant reduction in the intestinal damage (L/M test: 0.06569 ± 0.01821 vs. 0.04350 ± 0.00803; N = 13; p = 0,03). These results demonstrate that Gin and Ala had a better effícacy than Glu in the intestinal Na transport. The ORS-Gln was more efficient than ORS-control in the secretory diarrhea induced by choleratoxin. AGG was stable in acidic conditions and was able to increase intrestinal water and electrolyte transport. ORS-Gln was able to decrease intestinal damage in high risk children or children with diarrhea.